Escape to victory on the stock market : impact of soccer game outcomes on the club's stock price - Neudl, Manfred (My University, 2014)
The study focuses on game outcomes of the national Championship of stock listed soccer clubs and their influence on the stock price. This paper examines 13 clubs of 6 different countries which count to the top-teams in Europe. The data set includes 13 seasons, from 2000/2001 to 2012/2013. This study contributes to previous studies and show new aspects of the impact of soccer outcomes. This study investigates the impact of victories, draws and defeats on the stock price and on the trading volume. Particularities of stock price movements concerning the importance of last quarter of the season, of home/away games and of the goal difference are scrutinised. Moreover, it is tested whether there is a surprise effect while using betting odds. On the next trading the abnormal returns amounts to +0.48 % after victories, -1.05 % after draws and -1.28 % after defeats. During the season the trading volume is higher than in the off-season. Surprisingly the impact of soccer outcomes is stronger in the rest of the season than in the last quarter. There is also evidence for a home/away-games-, goal-difference- and a surprise effect.
Keywords: Behavioral Finance; Investor Sentiment; Soccer; Sport; Stock returns; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|